PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Nur Alfiatuz Zakiyah, Ahmaddah; Mujtahidin Mujtahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a digital flipbook learning medium based on local culture for the subject of Indonesian Cultural Diversity for fifth-grade students at Elementary School of Banyuajuh 3 Bangkalan. The research employed the Research and Development (R&D) method using the Borg and Gall model modified by Sugiyono through ten systematic stages, from problem identification to media production. The subjects were 28 students, with product trials involving 6 students and usage trials involving 22 students. Data were collected through validation questionnaires, practicality questionnaires, learning outcome tests and personality inventories. Validation results showed the flipbook was categorized as “very valid” by subject matter experts (89.70%) and media experts (97.72%), and “valid” by design experts (80.55%). Practicality was rated very high by teachers (90.62%) and students (85.68%). Effectiveness was demonstrated by an increase in classical completion rates from 42.86% to 86.36%, along with personality inventory results in the “very good” category for love of homeland (89.54), tolerance (95.07), and responsibility (94.88). Therefore, the digital flipbook proved valid, practical, and effective as an interactive learning medium while also strengthening students’ cultural literacy.